THE INCIDENCE OF CLINICAL AND SUBCLINICAL MASTITIS IN DIARY COWS AT THE DRY PERIOD IN BAGHDAD - A. Yass, A.; A. Al-Izzi, S.; Sh. Sultan , A. (The Iraqi Journal of Veterinary Medicine, 1994)
The present study was conducted on onc hundred twenty non-lactating COWS located in two different regions in Baghdad. The overall incidence of clinical and subclinical mastitis was found to be 10.0% (5.26% on quarter basis) and 30.47% (11.43% on quarter basis) respectively. Bacteriological examination of 401 milk Samples revealed that Staphylococcus aureus was the cheif etiological agent (36.15%), both in clinical and subclinical mastitis followed by Streptococcus agalactiae (21.69%), Escherichia coli (13.25%), Streptococcus dysglactiae (9.64%), Streptococcus uberis (6.02%), Corynebacterium pyogenes (6.02%), Klebsiella pneumoniae (2.41%), Staphylococcus epidermidis (2.41%) and Pseudomonas aeruginosa (2.41%). It was noticed that, the udder infection was high during the first and last two weeks of the dry period (14.16% and 24.16% respectively)